5-n-alkylresorcinols but not hydroxycinnamic acids are directly related to a lower accumulation of deoxynivalenol and its glucoside in Triticum spp. Genotypes with different ploidity levels. (January 2019) - Righetti, Laura; Cirlini, Martina; Folloni, Silvia; Ranieri, Roberto; Galaverna, Gianni; Bertuzzi, Terenzio; Dall'Asta, Chiara; Battilani, Paola; Giorni, Paola
Abstract: This study aimed to investigate the possible correlation between 5-n-alkylresorcinols and hydroxycinnamic acids on mycotoxin accumulation in grains under field conditions. At this purpose, ten different grain varieties characterized by different degree of ploidy (hexaploid, tetraploid, diploid) were chosen, among them common and durum wheat, einkorn, emmer, and spelt. The contamination, expressed as the sum of DON and DON3Glc, was found to be significantly lower in common wheat and spelt than in emmer, durum wheat and einkorn, following a trend hexaploid < tetraploid < diploid species. The mycotoxins content negatively correlated with the total 5-n-alkylresorcinols and the ratio AR21:0/AR23:0, recently reported as an indicator of antifungal activity. Interestingly, DON3Glc was negatively correlated with the ratio AR17:0/AR21:0, reported as a genetic-related indicator, in agreement with its biological role; in fact, it is formed in plant as detoxification product. On the contrary, no correlation was pointed out with total and free HCA. The results obtained indicated that only the lipophilic phenolic fraction in wheat could exert an inhibitory effect towards mycotoxin accumulation. Highlights: The correlation between lipophilic phenolic fraction and mycotoxin was studied. The contamination followed the trend hexaploid < tetraploid < diploid wheat species. 5-n-alkylresorcinols were associated with a lower accumulation of deoxynivalenol. No correlation was pointed out with total and free HCA.